Pengaruh Profitabilitas dan Skala Usaha terhadap Nilai Perusahaan Sektor Perbankan di Indonesia - Nurul Hidayat; As’adi Khas; Buhairi Buhairi; Nur Diana Khalida; Rahmat Zulkarnain; Wakik Wakik (JIOSE: Journal of Indonesian Sharia Economics, 2026)
This study analyzes the effect of profitability and firm size on firm value in the banking sector in Indonesia, and evaluates its implications for the stability of the national financial system. Profitability is measured using Return on Assets (ROA), while firm size is proxied by the natural logarithm of total assets. Firm value is measured using Price to Book Value (PBV). The data were obtained from 43 banks listed on the Indonesia Stock Exchange (IDX) in 2024, selected using a purposive sampling method, and analyzed using multiple linear regression. The results show that profitability has a positive and significant effect on firm value, indicating that strong financial performance enhances investor perception and strengthens corporate resilience. In contrast, firm size has a negative and insignificant effect, which may reflect potential inefficiencies in large-scale banks. Simultaneously, both variables have a significant effect on firm value, although the model explains only 18.06% of the variation in firm value. These findings underscore the importance of strengthening profitability as the primary foundation of firm value in the banking sector.